p21-activated Kinase 6 (PAK6) Inhibits Prostate Cancer Growth via Phosphorylation of Androgen Receptor and Tumorigenic E3 Ligase Murine Double Minute-2 (Mdm2) - Tong Liu; Yang Li; Hui Gu; Ge Zhu; Jiabin Li; Liu Cao; Feng Li (2012)
The androgen receptor (AR) signaling pathway plays a crucial role in the development and growth of prostate malignancies. Regulation of AR homeostasis in prostate tumorigenesis has not yet been fully characterized. In this study, we demonstrate that p21-activated kinase 6 (PAK6) inhibits prostate tumorigenesis by regulating AR homeostasis. First, we demonstrated that in normal prostate epithelium, AR co-localizes with PAK6 in the cytoplasm and translocates into the nucleus in malignant prostate. Furthermore, AR phosphorylation at Ser-578 by PAK6 promotes AR-E3 ligase murine double minute-2 (Mdm2) association, causing AR degradation upon androgen stimuli. We also showed that PAK6 phosphorylates Mdm2 on Thr-158 and Ser-186, which is critical for AR ubiquitin-mediated degradation. Moreover, we found that Thr-158 collaborates with Ser-186 for AR-Mdm2 association and AR ubiquitin-mediated degradation as it facilitates PAK6-mediated AR homeostasis. PAK6 knockdown promotes prostate tumor growth in vivo. Interestingly, we found a strong inverse correlation between PAK6 and AR expression in the cytoplasm of prostate cancer cells. These observations indicate that PAK6 may be important for the maintenance of androgen-induced AR signaling homeostasis and in prostate malignancy, as well as being a possible new therapeutic target for AR-positive and hormone-sensitive prostate cancer.